(3GdJVdjd GdEYdGej (B:s (3cja jbhe GdEYdGe HJSWjM KbGaI GdLeGgjQ hJZjjH GdhYj (B: (3OQGSI fbOjI JMdjdjI dhGbY GdEYdGe GdeYGUQ (B/s - (3HYRjR, EHQGgjes ((3GdbGgQI (B:s (3OGQ GdcJGH GdMOjK ,s, 2015)
(3JfGhdfG ajg aUhd h eMGhQ MjK HOGfG GdaUd(B1 (3HGdMOjK Yf GdEYdGe GdehLg h MOOfG eagheg h GTcGdg HGdEVGaI Zdi GdLhGfH GdJj JMGhd GdEYdGe HGdEVGaI Edi GdLhGfH GdJj JJONd ajgG gPg GdGWQGa h bO JWQbfG aj GdaUd (B2 (3Gdi eaghe GdJVdjd GdGYdGej h Gge GdJbfjGJ h GdGSGdjH GdeYJeOI ddJXdjd h GdGKGQ h GdGfYcGGJ GdeJQJHI h bO NUfG GdaUd (B3 (3ddMOjK Yef eSGgeI GdGYdGe GdeYGUQ aj UfGYI GdNHQ h HGdJGdj OhQg aj UfGYI GdhGbY GeG GdaUd (B4 (3abO JfGhdfG ajg GdeeGQSGJ GdJVdjdjI aj hSGFd GdGYdGe GdZQHjI ShGA GdMedGJ GdSjGSjI Gh aj GdMQhH h GdJONdGJ GdYScQjI GdJj JNhVgG GdOhd GdZQHjI YeheG h GdhdGjJ GdeJMOI GdGeQjcjI NUhUG h aj GdaUd GdNGeS JWQbfG Gdi GdJVdjd GdeeGQS aj GdGYdGe GdYQHj HeNJda GTcGdg h GfeGWg h aj GdaUd (B6 (3JWQbfG Gdi OhQ GdGYdGe GdLOjO aj GdeeGQSI GdJVdjd GdGYdGej ef NdGd eNJda GdehGbY h GdJWHjbGJ GdGdcJQhfjI GdeSJYedI h aj GdaUd GdGNjQ bOefG YfGUQ JNU GdGYdGe GdefThO GdPj JWGdH Hg eNJda GdGWQGa GdLeYjGJ GdGMRGH GdGYdGejhf h GdcJGHs
(3HjHdjhZQGajI(B:(3U(B.223-239s
Keywords: (3GdEYdGe GdeYGUQs; (3GdJVdjd GdEYdGej s; (3GdLhGfH GdCNdGbjI h GdOjfjIs; (3OQGSI GdfbOjIs